Early dementia--optimal management in general practice - Workman, Barbara; Dickson, Fiona; Green, Sally (Australian family physician, 2010)
The assessment and management of dementia is complex. General practitioners are often the first point of contact for people with dementia, and their families. General practitioners have a key role in providing quality primary care in terms of the identification, assessment, provision of information, referral and ongoing management. This article discusses the role of the GP in the diagnosis and management of people with dementia. It is important GPs are aware of the importance of early detection of dementia. Dementia is a complex condition. It develops slowly and early signs of dementia are very subtle. Difficulty in detecting the transition between normal aging and the onset of dementia and the lack of a definitive diagnostic tool often precludes early diagnosis. Evidence based recommendations are available to assist GPs in the diagnosis and ongoing management of people with dementia.